Land covers and climate impacts on land surface temperature in Putrajaya, Malaysia / Siti Aekbal Salleh … [et al.] - Salleh, Siti Aekbal; Abd.Latif, Zulkiflee; Wan Mohd, Wan Mohd. Naim; Chan, Andy (Universiti Teknologi MARA Cawangan Selangor, 2018)
This study investigates the influence of surface heterogeneity to the land surface temperature (LST). The land cover changes evaluation and historical climate data comparison were used in this study. Land cover, Normalised Difference Vegetation Index (NDVI), Normalised Difference Built-up Index (NDBI) and LST maps are produced to quantify the impacts of urbanization towards the surface thermal behaviour. The urbanization was set on years 1999 to 2006. While urbanization continued in 2009, the surface temperature was lower than that of 2006. The sea level was notably high during 2006, suggesting the lost of ice extent and evident to the climate change effects. Therefore, the fluctuation of temperature in 1999 to 2009 manifestly influenced by green space and climatic response and not solely caused by urbanization.